Pengaruh Tingkat Pendidikan, Kompetensi dan Komunikasi Terhadap Organizational Citizenship - Muh. Taufik Donny Pratama; Aftoni Susanto; Agus Siswanto (Economic Reviews Journal, 2025)
Human resources remain a focal point for organizations in their efforts to survive and compete in an increasingly competitive environment. One of the primary concerns of managers in enhancing organizational effectiveness is employee behavior in the workplace. Human resources serve as a crucial element within organizations, playing a significant role in achieving organizational goals. Beyond merely assisting organizations in reaching their objectives, human resources also contribute to defining attainable and effective goals based on the available resources. This study aims to examine the influence of education level, competence, and communication on Organizational Citizenship Behavior (OCB) at Yellow Star Hotel Gejayan. The research adopts an associative approach using quantitative methods. The sample consists of 122 employees working at Yellow Star Hotel Gejayan. The results of the analysis indicate that education level has a significant impact on Organizational Citizenship Behavior at Yellow Star Hotel Gejayan. Additionally, competence and communication also exhibit a significant influence on Organizational Citizenship Behavior at the hotel.